A hybrid MCDM model encompassing AHP and COPRAS-G methods for selecting company supplier in Iran - Zolfani, Sarfaraz Hashemkhani; Chen, I-Shuo; Rezaeiniya, Nahid; Tamošaitienė, Jolanta (Technological and Economic Development of Economy, 2012)
This paper is aimed at utilizing a hybrid multi-criteria decision making (MCDM) model for selecting a supplier. First, eight evaluation criteria, including cost, quality, distance, delivery reliability, reputation, technology level, compatibility and development ability are identified. The A nalytic H ierarchical P rocess (AHP) is initially used for calculating the weight of each criterion. The CO mplex PR oportional AS sessment of alternatives to G rey relations (COPRAS-G method) is adopted for ranking and selecting suppliers. In order to illustrate the functional ability of the developed model, Kalleh Company is chosen as a case study and can be used as a pattern for supplier selection and future researches.